The The implementation of the contextual teaching and learning (CTL) model on algebra learning, is it effective? This research discusses the application of the Contextual Teaching and Learning (CTL) model in algebra learning and its effectiveness. Starting by explaining the basic concepts of CTL, this article then highlights the importance of algebra in education and the challenges of its teaching. The main characteristics of CTL, such as problem-based learning and engagement with the real world - uswatun (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This research aims to find out the influence of the application of the Contextual Teaching and Learning (CTL) approach on the quality of mathematics learning in algebraic materials. Mathematics is often considered difficult by students, so an approach is needed that can increase student understanding and motivation. The CTL approach connects the material with real-life situations, which can make learning more meaningful and relevant for students. In the previous research they used several methods including experimental design with pretest-posttest control group design. In the experimental group they were taught using the CTL approach, while the control group used conventional learning methods. The instruments used include pretest and posttest tests, observations, and questionnaires to measure student involvement and perception. The results of the study show that the application of CTL can increase the understanding and involvement of students in learning algebraic materials, as well as improve their mathematical reasoning skills. Therefore, the CTL approach is proven to be effective in improving the quality of mathematics learning in high school students.